Anomaly inflow for M5-branes on punctured Riemann surfaces - Bah, I; Bonetti, F; Minasian, R; Nardoni, E (Springer Nature, 2019)
We derive the anomaly polynomials of 4d $\mathcal{N}$= 2 theories that are obtained by wrapping M5-branes on a Riemann surface with arbitrary regular punctures, using anomaly inflow in the corresponding M-theory setup. Our results match the known anomaly polynomials for the 4d $\mathcal{N}$= 2 class S SCFTs. In our approach, the contributions to the ’t Hooft anomalies due to boundary conditions at the punctures are determined entirely by G4-flux in the 11d geometry. This computation provides a top-down derivation of these contributions that utilizes the geometric definition of the field theories, complementing the previous field-theoretic arguments.